Scientific Authority in Iranian Pharmaceutical Sciences Research Centers: The Results of a Decade Research Evaluation: Scientific Authority in Pharmaceutical Research Center - Baradaran Eftekhari, Monir; Falahat, Katayoun; Ashouri, Sahar (Iranian Journal of Pharmaceutical Sciences, 2024)
The scientific authority refers to social power of scientific knowledge, in different sciences. The aim of this study is to present the role of Iranian pharmaceutical research centers in scientific authority based on research evaluation for a decade. Iranian pharmaceutical research centers with more than one year of activity from 2013 to 2022 were assessed based on the intervention model of evaluation system. Three domains including stewardship, knowledge production and research impact with 20 indicators have been used in this process. 36 pharmaceutical sciences research centers (PhRCs) related to 23 universities of Medical Sciences (UMSs) were evaluated for a decade. The mean and standard deviation (SD) of age of the research activities in PhRCs was 12.2 ± 8.60. The ratio of faculty member to research center was 10.5. The total number of published articles was 20166 and 70% of which were indexed in ISI –WOS.34.2% and 21.7% of them were published in the first quantile journals and with international collaboration respectively. Based on research ranking, the first three centers were Tabriz Applied Pharmaceutical Science Research Center, Mashhad Pharmaceutical Sciences Research Center and Tabriz Pharmaceutical Nanotechnology research center. Mission oriented research activities in Iranian pharmaceutical research centers may lead them in achieving scientific authority.